2020
DOI: 10.1186/s12889-020-08645-1
|View full text |Cite
|
Sign up to set email alerts
|

Active play in ASP –a matched-pair cluster-randomized trial investigating the effectiveness of an intervention in after-school programs for supporting children’s physical activity

Abstract: Background: Interventions directed at after school programs (ASPs) have the potential to support physical activity (PA) in young children. Research has indicated that interventions that emphasize competence building among the ASP staff can lead to increased PA among the children. The present study evaluates the effectiveness of the Active Play in ASP intervention-a program for ASP staff aimed at supporting physical activity among first graders in ASP. Methods: We used a matched-pair cluster randomized design a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…More comparable results to the ones reported here were found in a one-year school-based intervention study in the Netherlands [57] as well as a recent Scandinavian study in first graders, intervening on teacher level in an after school care setting [61]. Similar to this study, teachers in Norway were trained to create a physical activity supporting environment in order to promote physical activity and reduce sedentary time.…”
Section: Discussionsupporting
confidence: 82%
“…More comparable results to the ones reported here were found in a one-year school-based intervention study in the Netherlands [57] as well as a recent Scandinavian study in first graders, intervening on teacher level in an after school care setting [61]. Similar to this study, teachers in Norway were trained to create a physical activity supporting environment in order to promote physical activity and reduce sedentary time.…”
Section: Discussionsupporting
confidence: 82%
“…This study also has some limitations, such as the presence of 39% missing data within PA variables due to children moving to another school, dropping out from the study, not wearing the monitor enough to obtain a valid a PA measurement, or losing the accelerometer during the assessment period. However, the amount of missing data reported in this in this study is similar to that reported in previous research using device-based measurements of PA [106,107]. A further limitation is that most of the children did not wear the monitor overnight and that there was low compliance from parents with filling in PA wear time diaries, leading to the impossibility to calculate the waking time for each individual.…”
Section: Discussionsupporting
confidence: 72%
“…Second, despite clear gender and race differences in youth MVPA at baseline, gender and race were not signi cant predictors of adolescents' daily MVPA change trajectories, suggesting that across gender and race, youth had a similar rate of change in MVPA across the 16-week intervention. Third, change in intrinsic motivation, but not autonomous extrinsic motivation, was a signi cant predictor of adolescents' daily MVPA changes.Although there are signi cant bene ts of MVPA to the health and well-being of youth(Fullmer et al, 2018) and ASPs are an ideal setting to support youth recommended daily PA accrual, several ASPs intervention studies that have aimed to increase adolescent MVPA through improving the motivational climate have reported a lack of adequate daily MVPA and challenges with maintaining children's attendance over time(Riiser et al, 2020;Wilson et al, 2011). Grounded in SDT, the Active Play Trial emphasized the necessity of retaining the self-chosen and child-managed character of play, as well as supporting the children's need for competence, relatedness, and autonomy(Riiser et al, 2020).…”
mentioning
confidence: 99%
“…Third, change in intrinsic motivation, but not autonomous extrinsic motivation, was a signi cant predictor of adolescents' daily MVPA changes.Although there are signi cant bene ts of MVPA to the health and well-being of youth(Fullmer et al, 2018) and ASPs are an ideal setting to support youth recommended daily PA accrual, several ASPs intervention studies that have aimed to increase adolescent MVPA through improving the motivational climate have reported a lack of adequate daily MVPA and challenges with maintaining children's attendance over time(Riiser et al, 2020;Wilson et al, 2011). Grounded in SDT, the Active Play Trial emphasized the necessity of retaining the self-chosen and child-managed character of play, as well as supporting the children's need for competence, relatedness, and autonomy(Riiser et al, 2020). The Active Play Trial showed no signi cant intervention effects were observed for children's MVPA in ASPs compared with control programs(Riiser et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation